Acute toxicity test and lethal dose (LD50) from a combination of sambiloto extracts (Andrographis paniculate) and catfish oil (Pangasius micronema Blkr.) in mice - Rinanda Al Rissa Rizki Hera; Meitasari Annisa Diyan; Sasongko Heru (BIO Web of Conferences)
Sambiloto (Andrographis paniculata) contains andrographolide compounds, which have anti-inflammatory properties. On the other hand, catfish oil (Pangasius micronema Blkr.) contains DHA and EPA compounds known to be unsaturated fatty acids and have antiinflammatory properties. Sambiloto extracts and catfish oil will be combined to determine the pharmacological effects caused by an acute toxicity test to determine the toxicity and LD50 value of the combination of extracts. This research is conducted experimentally, utilizing mice as test animals. The extract was administered for 14 days, and symptoms of toxicity were observed, including the number of animals that died, body weight, and the weight of the liver, kidneys, and heart. The data was then tested using the Thompson-Weil method and statistical tests using the oneway ANOVA test and continued with the Tukey post hoc test. The toxicity test results indicated toxicity symptoms at the highest dose, but the combination of extracts’ LD50 value was pseudo-LD50, implying that test animals could theoretically still receive the highest dose value. The statistical analysis revealed no significant differences in the body and organ weight of the mice, indicating that this research could still use the combination of the two extracts up to the highest dose.